A concept analysis of intercultural communication. Issue 4 (2nd June 2021) - Mosed, Hameedah; Periord, Madison; Caboral‐Stevens, Meriam
Abstract: Aim: To explore the concept of intercultural communication. Background: As global migration increases, countries around the world are starting to see diversity among their population. With this increasing multicultural society, effective communication is crucial, particularly in the area of healthcare. Intercultural nursing requires nurses to care for patients of various cultural backgrounds by considering their cultural needs. It is critical for nurses to be able to communicate effectively with patients of various cultures to provide care that is holistic and culturally appropriate to the diverse population. Methods: Walker and Avant's eight‐step approach to concept analysis. Results: Intercultural communication in nursing is face‐to‐face, verbal or nonverbal communication that occurs between people of different cultures. Its defining attributes are (1) meeting between language and culture for a specific purpose and (2) face‐to‐face (in‐person or virtual) human interaction between individuals from different cultures. Antecedents of intercultural communication in nursing are globalization, technology, and social environment. Consequences include reduced ethnocentrism and negative stereotyping. Empirical referents depict the existence of the concept, which includes several tools developed as a means to measure or evaluate intercultural communication. Conclusion: This study presented the defining attributes, antecedents and consequences, model case, and empirical referents of intercultural communication.